Perceived effect of warning label on parental food purchasing and drivers of food selection among South African parents–An exploratory study - Bopape, Makoma; Taillie, Lindsey Smith; Swart, Rina (Frontiers in Public Health, 2022)
Household food purchasing decision is a complex process influenced by factors such as marketing, cost, children food preference and parental choices. Most food products targeted towards children are unhealthy and are aggressively marketed to increase desirability among parents and children making healthier food selection even harder . The warning label (WL) is identified as a simple front-of-package labelling format that assist consumers to easily identify unhealthy foods and reduce their purchasing. This was a qualitative study that aimed to investigate the perceived effect of the warning label (WL) on parental food purchasing and drivers of food selection among parents. The study was conducted in a mainly rural part of South Africa, in Limpopo Province. Data were collected from 44 adult participants, all parents with children aged below 16 years selected using the snowball sampling method. Seven focus groups diversified according to age, literacy, income and urbanicity were utilised for data collection. Using a focus group discussion guide, parents were shown images of six products (crisps, soda, juice, biscuits, cereals and yoghurt) superimposed with the WL and questions asked were based on those images. Thematic analysis revealed that although some parents felt undeterred by the WL, some felt they would alter their food purchasing in the presence of the WL. Other parents felt they would reduce the frequency or the amount purchased or completely stop purchasing labelled products for their children. Motives behind perceived behaviour modification included children’s health being perceived as a priority and labelled products being viewed as unhealthy. Factors such as pressure from children, taste, poor nutrition knowledge and affordability seemed to influence parental food selection. These findings have important policy implications by providing evidence to policymakers that the WL may alter parental food purchasing and also provide insight into drivers of food selection among South African parents.